If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = -1K + 8 Reorder the terms: 15 = 8 + -1K Solving 15 = 8 + -1K Solving for variable 'K'. Move all terms containing K to the left, all other terms to the right. Add 'K' to each side of the equation. 15 + K = 8 + -1K + K Combine like terms: -1K + K = 0 15 + K = 8 + 0 15 + K = 8 Add '-15' to each side of the equation. 15 + -15 + K = 8 + -15 Combine like terms: 15 + -15 = 0 0 + K = 8 + -15 K = 8 + -15 Combine like terms: 8 + -15 = -7 K = -7 Simplifying K = -7
| 6n-14=4n+20 | | x+x+4=9 | | n3/2=125 | | 3/7x-11=-4/7x | | 4/x-3 | | -6=y/5-9 | | -1B+2=.5 | | -5*30-5y=25 | | 3y+9=8y-16 | | 3x+(-5)=7 | | -6+4n=2n+6 | | -50-6= | | -5*25-5y=25 | | 5x+30=8x | | 4(k-5)+6(k+5)=30 | | 19=a+h | | (4/x)+(x-3/2x+3)=3 | | 9/x=51/34 | | 2(y^2-2y-4)=-y^2+y | | x^2+27=-9 | | 19=2(4a) | | 2x+31+3x=-19 | | 35+2y=10 | | 3a-8a-4a=21 | | ((2x-7)/7)14 | | (8/x)-(x/18)=0 | | (x-7)(2x+8)=0 | | (2x-7/7)14 | | (-6p+7)x-4= | | -(23+x)=7(x-1) | | 4x+(5y+6x)= | | x^4+4x^3+5x^2=0 |